Peripheral blood hypereosinophilia masquerading a case of acute lymphoblastic leukemia - Reddy, Suganya Kuppovi; Mishra, Pritinanda; G, Maya; K, Arun; Jacob, Sajini Elizabeth; W, Jyoti; Hamide, Abdoul; Basu, Debdatta; Dubashi, Biswajit (Annals of Pathology and Laboratory Medicine, 2015)
Acute lymphoblastic leukemia (ALL) usually presents with fever, pallor, lymphadenopathy, hepatosplenomegaly and presence of lymphoblasts in the peripheral blood and bone marrow. ALL presenting as peripheral blood hypereosinophilia is a rare entity with less than 50 cases reported since 1973. It is a distinct clinico-pathologic entity with specific cytogenetic abnormalities. It is important for clinicians and the pathologists to be aware of the specific manifestation of ALL with eosinophilia. We report a case of ALL with peripheral blood eosinophilia. A 39 year male presented with fever, cough with expectoration and dyspnoea. There was no past history of allergies, skin rash or parasitic infection. On examination there was hepatosplenomegaly with no lymphadenopathy. Chest X ray showed diffuse reticular pattern throughout the lungs. Peripheral smear examination revealed high leucocyte count (52,900/mm3) with eosinophils constituting 89% (AEC- 47740/mm3). No atypical cells or hemoparasites were seen. Stool examination for parasites and filarial serology were negative. Bone marrow examination, however, showed blasts constituting 90%. Blasts were positive for TdT, CD20, CD10 by immunocytochemistry and a diagnosis of precursor B cell ALL was made. The patient was started on treatment. Cytogenetic analysis was also done. Hypereosinophilia can mask many underlying pathologies, of which ALL is a rare condition. As this condition usually presents with absence of blasts in the peripheral blood, there may be delay in diagnosis.So, in patients with persistant hypereosinophilia where there are no contributory causes, a bone marrow examination is a must for an accurate diagnosis.